LEGAL INFRASTRUCTURE FOR SUPPORTING SMALL AND MEDIUM BUSINESSES IN THE U.S. - Vyshyvaniuk, Yuliia (Global Prosperity, 2025)
Abstract. The article explores the functioning of the legal infrastructure that supports small and medium-sized businesses in the United States, focusing on its institutional elements, legal mechanisms, and informational support for entrepreneurial activity. The aim of the article is to analyze the legal infrastructure supporting small and medium-sized enterprises in the U.S., its institutional framework, functional components, and information-based mechanisms that contribute to the sustainable development of entrepreneurship. The study employed general scientific methods of cognition: analysis; synthesis; induction; deduction; comparison; generalization; systematization. The findings show that small and medium-sized businesses in the U.S. play a strategic role in the country’s socio-economic development, accounting for over 99% of business entities, generating nearly half of private-sector employment, and significantly contributing to GDP formation. The U.S. model of SME development is characterized by a stable level of entrepreneurial activity; a dominant service sector; a high rate of self-employment; strong adaptability to market changes. However, at the current stage, SMEs face a range of challenges, including rising costs; labor shortages; limited access to financial resources; significant regulatory pressure, which highlights the need for targeted government support. The study concludes that the legal infrastructure plays a central role in the SME support system, integrating regulatory frameworks, advisory and educational support, access to legal services, and digital tools. It is shown that the key components of this system include compliance with legal requirements related to registration, licensing, tax and labor regulations, as well as mechanisms for protecting consumer rights and intellectual property. The practical significance of the study lies in the potential to apply U.S. experience in improving legal and informational support systems for SMEs in other countries, particularly within transitional economies.